Edukacja regionalna w dobie globalizacji. Problem budowania wspólnot lokalnych – wybrane aspekty - Marceli Tureczek (In Gremium. Studies in History, Culture and Politics, 2020)
Politics and regional education suffer from a lack of integration and short-term dependence on political and economic factors. In practice, we are dealing with a low, fragmented level of regional activity, which should create coherence of economic policy and social policy. Both of these factors are as much as possible within the above considerations and at the same time refer to the state policy as to the activity and innovation of local governments. Regional policy, especially at the local government level and regional education - as a network of connections, may not only be a response to threats of globalization processes for local communities, but may and should also be a factor stimulating the activity or the attitude of reinvestment of representatives of local communities, contributing as a whole to improving the condition of small regions. These possibilities in the area of ​​building cultural capital are still poorly understood at the national and local government level and thus insufficiently used.